2017
DOI: 10.3390/app7030283
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Preliminary Design Method for Subsonic Splittered Blades in Highly Loaded Axial-Flow Compressors

Abstract: This paper presents a model for predicting the reference minimum-loss incidence and deviation angles of a blade arrangement with splitter vanes, which is probably a solution for future ultra-highly loaded axial compressor designs. The motivation of the modeling is to guide the blading design in splittered compressor design processes where the additional splitter vanes must be specially considered. The development of the model is based on a blade performance database from systematic numerical simulations. Basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Previous studies only treated splitter vanes as the equivalent of blade solidity changes, such as the concepts of equivalent solidity or effective blade number. The former is discussed in splittered axial compressor rotor researches [19][20][21] and the latter is used in centrifugal impeller designs. 5 These two concepts are proved to be equivalent.…”
Section: Research Object and Methodsmentioning
confidence: 99%
“…Previous studies only treated splitter vanes as the equivalent of blade solidity changes, such as the concepts of equivalent solidity or effective blade number. The former is discussed in splittered axial compressor rotor researches [19][20][21] and the latter is used in centrifugal impeller designs. 5 These two concepts are proved to be equivalent.…”
Section: Research Object and Methodsmentioning
confidence: 99%
“…Hence, separation in smaller radial gap sizes happens earlier, and it is bigger than that of higher radial gap size (Figure 20). Liu et al [36] also showed that the compressor performance deterioration is the result of this supersonic acceleration and notable shock waves interaction with boundary layers. Figure 19 represents the effect of the radial gap ratio on the shock wave structure on the basis of absolute Mach number contours superimposed with isoclines at the mid-span of the vane diffuser at Mu = 1.16.…”
Section: Effects Of Radial Gap Ratio On Vaned Diffuser Performancementioning
confidence: 99%
“…Hence, separation in smaller radial gap sizes happens earlier, and it is bigger than that of higher radial gap size (Figure 20). Liu et al [36] also showed that the compressor performance deterioration is the result of this supersonic acceleration and notable shock waves interaction with boundary layers. However, according to Figure 20, as the impeller inlet tip-speed Mach number is less than the unity value (Mu = 0.69), the flow does not accelerate substantially.…”
Section: Effects Of Radial Gap Ratio On Vaned Diffuser Performancementioning
confidence: 99%
“…The studies carried out by Tzuoo et al., 14 Qiu et al., 15 and Liu et al. 16 indicates that the pressure ratio increase and loss reduction are achieved by splittered axial compressors under the highly loaded condition. In addition, splitter blades have been also used by Lavagnoli et al., 17 Yasa et al., 18 Spataro et al., 19 and Clark et al.…”
Section: Introductionmentioning
confidence: 97%